2016
DOI: 10.21475/ajcs.2016.10.10.p7455
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical changes in guava raisin (Psidum guajava l.) produced by osmotic dehydration and drying convective

Abstract: The osmotic dehydration pre-treatment is used to partially reduce the fruit initial water content, before convective drying. Purpose of the present work is to investigate the influence of osmotic treatment followed by convective drying on the physicochemical parameters of guava slices. The Paluma guava was cut into slices of 3.0 × 2.0 × 0.9 cm, dehydrated and dipped in sucrose syrup at concentrations of 40, 50 and 60 °Brix, at temperatures of 30, 40 and 50 °C. The process was again supplemented by convective d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…The consumer expects a processed product with characteristics similar to or better than the raw material. De Castro et al [48] confirmed the influence of osmotic dehydration on the properties of guava, at the same time showing the influence of the temperature used on the color of the obtained droughts and thus on the sensory properties and consumer acceptability. In the conclusions, the authors stated that the dehydrated fruit retained its color while drying, especially of products containing a higher sugar content, resulting, among others, from dehydration in a sucrose solution, were characterized by a much darker color, which in relation to some fruit is not acceptable for the consumer.…”
Section: Discussionmentioning
confidence: 83%
“…The consumer expects a processed product with characteristics similar to or better than the raw material. De Castro et al [48] confirmed the influence of osmotic dehydration on the properties of guava, at the same time showing the influence of the temperature used on the color of the obtained droughts and thus on the sensory properties and consumer acceptability. In the conclusions, the authors stated that the dehydrated fruit retained its color while drying, especially of products containing a higher sugar content, resulting, among others, from dehydration in a sucrose solution, were characterized by a much darker color, which in relation to some fruit is not acceptable for the consumer.…”
Section: Discussionmentioning
confidence: 83%
“…Angelini [18], reported similar values in osmotic kiwi dehydration, which presented higher pH values than natural fruit. However, De Castro et al, [19] has different results in the osmotic dehydration of the guava slices, they present a small decrease in pH, which was attributed to a concentration of hydrogen ions caused by the elimination of water. In contrast, Bernardi et al, [20] did not report significant differences between the pH values obtained for natural mango fruits and for osmodehydrated fruits, which indicates that during the osmotic dehydration process there was no difference in the loss of organic symptoms.…”
Section: Ph Variationmentioning
confidence: 95%
“…Ferreira et al (2020) obtiveram valores de difusividade variando de 1,268 a 1,976 x 10 -9 m s -1 para cubos de mamão osmodesidratado a 50 °Brix e 60 °C quando a temperatura de secagem variou de 50 a 70 °C. Aires et al (2016) observaram valores de difusividade de 3,19 x 10 -10 m s -1 para cubos de maçã desidratados a 40 °Brix e 40 °C. Para , na medida em que se aumenta o gradiente de temperatura, maior é o valor obtido para este parâmetro, pois em temperaturas inferiores como a de 50 °C as moléculas de água sofrem maior resistência ao sair do corpo devido a sua composição e estrutura física, fazendo com que a água fique mais ligada às moléculas que constituem a massa seca.…”
Section: Variáveisunclassified